2006
DOI: 10.1242/jcs.03262
|View full text |Cite
|
Sign up to set email alerts
|

The DNA helicase ChlR1 is required for sister chromatid cohesion in mammalian cells

Abstract: It has recently been suggested that the Saccharomyces cerevisiae protein Chl1p plays a role in cohesion establishment. Here, we show that the human ATPdependent DNA helicase ChlR1 is required for sister chromatid cohesion in mammalian cells. Localization studies show that ChlR1 diffusely coats mitotic chromatin in prophase and then translocates from the chromatids to concentrate at the spindle poles during the transition to metaphase. Depletion of ChlR1 protein by RNA interference results in mitotic failure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
114
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 40 publications
13
114
0
Order By: Relevance
“…A substantial fraction of cells (28% and 34% of the cells treated with RNAi constructs #5 and #7, respectively) also showed chromosome misalignment or missegregation (Supplementary Figure 3E). Since these phenotypes are ChlR1 is Required for Development and Chromosome Cohesion similar to the mouse phenotype and those published previously, 10 we concluded that the siRNA system was suitable for further studies.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…A substantial fraction of cells (28% and 34% of the cells treated with RNAi constructs #5 and #7, respectively) also showed chromosome misalignment or missegregation (Supplementary Figure 3E). Since these phenotypes are ChlR1 is Required for Development and Chromosome Cohesion similar to the mouse phenotype and those published previously, 10 we concluded that the siRNA system was suitable for further studies.…”
Section: Resultssupporting
confidence: 85%
“…In addition, depletion of either the cohesin molecule RAD21 or the ChlR proteins resulted in a loosened primary constriction or separated chromatids in HeLa cells. These studies verify the results of other ChlR1 RNAi studies 10 and are consistent with data obtained from our mutant mouse studies; as such, we have clearly eliminated the possibility that the effects of ChlR proteins on chromosome cohesion were artifacts encountered in siRNA experiments. Thus, we conclude that ChlR is required for centromeric cohesion in both mouse and human cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations